2016
DOI: 10.1007/s11356-016-7788-5
|View full text |Cite
|
Sign up to set email alerts
|

SO2-tolerant and H2O-promoting Pt/C catalysts for efficient NO removal via fixed-bed H2-SCR

Abstract: In this paper, Pt supports on carbon black powder (Vulcan XC-72) were synthesized via a hydrothermal method for selective catalytic reduction (SCR) of NO with H in the presence of 2 vol% O over a wide temperature of 20-300 °C. The results showed that the 3 and 5 wt% Pt/C catalysts resulted in high NO conversion (>90 %) over a temperature range of 120 to 300 °C, and the maximum NO conversion of 98.6 % was achieved over 5 wt% Pt/C at 120 °C. Meanwhile, the influence of SO and HO on the catalyst performance of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Cai et al 68 Some new materials, such as carbon and MOF, were also used as support for the preparation of H 2 -SCR catalysts. Tu et al 69 investigated Pt-supported XC-72 for NO reduction by H 2 with excess O 2 . The Pt/XC-72 catalyst exhibited high SO 2 resistance when the SO 2 concentration was below 260 ppm.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Cai et al 68 Some new materials, such as carbon and MOF, were also used as support for the preparation of H 2 -SCR catalysts. Tu et al 69 investigated Pt-supported XC-72 for NO reduction by H 2 with excess O 2 . The Pt/XC-72 catalyst exhibited high SO 2 resistance when the SO 2 concentration was below 260 ppm.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…[26][27][28][29] For gases at room temperature, alkaline substances are usually used as active materials, supported by impregnation method, to remove acid gas for feeding molten carbonate fuel cells (MCFCs). [30][31][32][33] Lee 34 showed that the HCl capacity of NaOH/AC is about 6 times that of commercial alumina. However, Micoli et al 35,36 investigated the HCl adsorption performance of activated carbon impregnated with KOH, NaOH or Na 2 CO 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%